Development of Abrasive Peeler cum Polisher for Ginger - Jain, N K; Doharey, D C; Sharma, K C (Journal of Agricultural Engineering, 2007)
World's 50% ginger is produced in India. Presently 2,63,170 MT of ginger is produced from an area of 77,610 ha. Peeling of ginger is a very tedious and time-consuming unit operation. Generally, ginger is peeled with knife or by rubbing against gunny bags or bamboo mats in order to fasten the drying process. Due care is required to avoid the loss of material during peeling. A simple hand operated abrasion type ginger peeler cum polisher was developed for facilitating the peeling and polishing at farm level. The machine has a perforated drum lined with emery strips at spacing of 25 mm. The drum is rotated manually at 45-50 rpm. It was observed that 74-81% peeling could be achieved with 5 kg batch in 8 to 12 min time. Around 2.5 to 3.8% material loss was recorded. Effective output of machine was found as 25-30 kg/h against 30 and 50 kg/day through manual and gunny bag peeling. The machine was also evaluated for polishing the dried rhizomes and it was found that surface of rhizomes gets smoothened due to friction and abrasion. The capacity for polishing was worked out as 50-60 kg/h. The cost of machine has been estimated as Rs 3000.